Filter Bank Multicarrier Modulation Techniques for 5G Communication Systems - Cheriat Mohamed; Achraf Ziam Saad Eddine; ENCA/ ZERDOUMI Zohra (University of M’sila, 2025)
This thesis investigates multicarrier modulation techniques for 5G telecommunications, comparing Orthogonal Frequency Division Multiplexing (OFDM) and Filter Bank Multicarrier (FBMC). It addresses 4G limitations, such as spectral efficiency and interference, and evaluates FBMC’s potential for 5G. Using MATLAB simulations, the study compares power spectral density (PSD), peak-to-average power ratio (PAPR), and bit error rate (BER). Results show FBMC’s superior spectral efficiency and lower PAPR, positioning it as a strong 5G candidate, though OFDM’s simplicity is advantageous in some cases. Future research on FBMC is recommended to optimize 5G performance.
Keywords: 5G; multicarrier modulation; OFDM; FBMC and Spectral Efficiency.